Izuchenie izmenenij otdelnykh fiziologicheskikh pokazatelej devushek pod vliyaniem zanyatij aerobikoj - Cheburaev, V. S.; Legostaev, G. N.; Izaak, S. I.; Chibissova, T. V. (Teorija i Praktika fiziceskoj Kul'tury, 2002)
The health of children and youth is worsened now under influence of factors of inadequate physical activity. The aim of this study was to reveal the imfluence of aerobics on the physiological parameters of girls. 15-17 aged girls participated in the research. Two groups participated in the experiment : in the first one girls were engaged in step-aerobics (11 person), in the second - improving and step-aerobics (13 person). The occupations passed 2 times per one week during 1 hour in the evening for one year. Taking into account the literary data on influence of aerobic exercises on an organism, and the results received in the work, it is possible to ascertain, that occupations by aerobics is one of the most accessible and effective means by the way of improving influence on an organism as they positively operate on physiological functions of an organism.